2018
DOI: 10.24198/kultivasi.v17i2.16914
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan beberapa jenis urin ternak sebagai pupuk organik cair dengan konsentrasi yang berbeda pada tanaman kelapa sawit (Elaeis guineensis jacq.) di pembibitan utama

Abstract: Pemanfaatan beberapa jenis urin ternak sebagai pupuk organik cair dengan konsentrasi yang berbeda pada tanaman kelapa sawit (Elaeis guineensis Jacq.) di pembibitan utama Utilization of livestocks urine as a liquid organic fertilizer with different concentrations on oil palm (Elaeis guineensis Jacq.) in main nursery Abstract. Seedling is an initial stage in the cultivation of oil palm, seed quality will affect the results that will be obtained later. Factor affecting the growth of seedlings of which the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
5
0
6
Order By: Relevance
“…This was due to the farmer used organic fertilizer from livestock (manure and urine) that lead to the increase of productivity (Table 1). Urine from livestock has been reported can give positive effect to the growth of oil palm [16]. Another group of researcher also reported that livestock give several benefit to the palm oil plantation in integration system that lead to the improvement of farmers income in Malaysia.…”
Section: Linking Crop and Livestock At The Farm Levelmentioning
confidence: 96%
“…This was due to the farmer used organic fertilizer from livestock (manure and urine) that lead to the increase of productivity (Table 1). Urine from livestock has been reported can give positive effect to the growth of oil palm [16]. Another group of researcher also reported that livestock give several benefit to the palm oil plantation in integration system that lead to the improvement of farmers income in Malaysia.…”
Section: Linking Crop and Livestock At The Farm Levelmentioning
confidence: 96%
“…The potential of liquid organic fertilizer production from goats in North Sumatera was 502,724,000 L/year (Table 1). Meanwhile, goat urine contains macronutrients of 1.13% N, 0.05% P2O5, 7.9% K2O [3] and other micronutrients. To obtain a better quality of liquid organic fertilizer, goat urine is usually first fermented with microorganisms.…”
Section: Potential Of Goat Manure Production In North Sumateramentioning
confidence: 99%
“…After 30 days of composting, the nutrient content reached 2.23% N, 1.24% P2O5, and 3.69% K2O [2]. Besides, goats also produce urine which contains nutrients such as 1.13% N, 0.05% P2O5, and 7.9% K2O [3].…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian Alvi et al, (2018) melaporkan kandungan urin sapi memiliki pH 8,25; N-total 0,23%; P2O5 0,07%; dan K2O 1,70% serta pemanfaatan urin ternak sebagai pupuk organik cair pada tanaman kelapa sawit dipembibitan utama tidak memberikan pengaruh terhadap pertumbuhan bibit kelapa sawit. Lubis & Sjofjan, (2016) menyatakan bahwa pemberian urine sapi berpengaruh tidak nyata terhadap tinggi bibit, jumlah daun, diameter bonggol, volume akar, rasio tajuk akar, tetap berpengaruh nyata terhadap bobot kering bibit kelapa sawit dengan konsentrasi urin sapi 60% menunjukkan bobot kering tertinggi.…”
Section: Pengaruh Urine Sapi Terhadap Pertumbuhan Bibit Tanaman Kelapa Sawit DI Pembibitan Awalunclassified